1984
DOI: 10.1530/acta.0.1070462
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone releasing factor infusion does not sustain elevated GH-levels in normal subjects

Abstract: To evaluate the dynamics of GH-secretion after infusion of growth hormone releasing factor, human pancreatic growth hormone releasing factor (hpGRF1-44) was infused over 2 and 5 h at a dosage of 100 \ g=m\ ghpGRF1-44/h into 11 healthy subjects. The infusion was started and terminated with a 50 \g=m\ghpGRF1-44 bolus injection. In 5 subjects 200 \ g=m\ g TRH was given 4 h after starting the infusion. In addition, 4 healthy subjects received 50 \g=m\ghpGRF1-44 bolus injection every 2 h. GRF, somatostatin, GH, Prl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
31
1

Year Published

1984
1984
1992
1992

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 15 publications
4
31
1
Order By: Relevance
“…The GH-stimulatory effect of repeated nocturnal GHRH injections is in accord with the effect of single and serial challenges during the daytime [23][24][25]. The only dif ference that emerged is that during the night the return of the plasma GH concentration to baseline is protracted, possibly because of enhanced responsivity of the somatotrophic system at this particular time.…”
Section: Discussionmentioning
confidence: 94%
“…The GH-stimulatory effect of repeated nocturnal GHRH injections is in accord with the effect of single and serial challenges during the daytime [23][24][25]. The only dif ference that emerged is that during the night the return of the plasma GH concentration to baseline is protracted, possibly because of enhanced responsivity of the somatotrophic system at this particular time.…”
Section: Discussionmentioning
confidence: 94%
“…The lessening of GH response to repeated GHRH stimula tion was shown not to be due to an increased metabolic degra dation or clearance of the neurohormone [3]. The existence of a GHRH-induced reduction in the GH releasable pool and/or the occurrence of a receptor or post-receptor mechanism of downregulation of somatotropes [5,6] were also hypothesized.…”
Section: Discussionmentioning
confidence: 99%
“…In normal adults repeated GHRH administration leads to progressively decreasing somatotrope response [2][3][4], A GHRH-induced selective reduction of the GH releasable pool or, alternatively, the occurrence of a receptor or post-receptor mechanism of downregulation of the somatotropes were hy pothesized [5,6], Other evidence supported the hypothesis that somatotrope refractoriness to repeated GHRH stimulation is due to elicitation of a negative autofeedback likely mediated by enhanced SRIH release [2,4,[7][8][9]. Particularly, in agreement with this hypothesis, it was shown that the enhancement of the cholinergic activity by pyridostigmine, a cholinesterase inhibitor likely acting by inhibition of SRIH [9][10][11], reinstates and even potentiates the GH responsiveness to a GHRH bolus preceded by another GHRH stimulation [4] as well as by administration of methionyl-GH [8].…”
mentioning
confidence: 99%
“…Thus, alternative explanations, relating to changes in the intracellular response to GRH or to changes in somatostatin secretion, appear more plausible. Other published data relating to plasma GRH levels after injection of exogenous GRH (32)(33)(34) are also likely to be incorrect, since the contribution of GRH metabolites to total measured GRH immunoreactivity is unknown. Finally, our results should be helpful in designing modifications of the GRH sequence that are resistant to enzymatic degradation in order to develop superactive analogs.…”
Section: Discussionmentioning
confidence: 99%